The anti-inﬂammatory effect of Phospholipase D 2 inhibition in an endotoxin-induced uveitis model - Tenconi, Paula Estefania (2025)
Purpose : Uveitis is an ocular inflammatory disease affecting the uveal tract and adjacent ocular structures, including the retina and the vitreous. This condition is estimated to account for ∼25% of blindness in developed countries. Our previous results demonstrated that the Phospholipase D (PLD) pathway mediates the inflammatory response of retinal pigment epithelium cells induced by lipopolysaccharide (LPS). This study aims to investigate the effects of PLD2 inhibition in ocular inflammation using an endotoxin-induced uveitis (EIU) animal model.